Is Kugel herniorraphy an option to laparoscopic hernia repair? - Çifter, C; Dogru, O; Çetinkaya, Z; Ilhan, YS; Bülbüller, N; Ali Akkus, M (Medimond S R L, 2000)
The aim of this clinical study was to compare the Kugel herniorrhaphy to laparoscopic hernia repair. Preperitoneal Kugel mesh hemiorraphy were performed to 22 patients inguinal hernia and laparoscopic hernia repair were performed to 20 inguinal hernia patients. In Kugel group; Operating time averaged 58 minutes (30-110 min) and mean age of the patients was 50 years (17-81). The only complication in Kugel group was a wound infection (4.5%). In laparoscopic group; Operating time averaged 82 minutes (51-130) and mean age of the patients was 46 years (21-73). There was 4 local complications (20%). Two mesh reactions, one hematoma and one seroma. In both group, the average return to routine activities was 7 days.and, no reccurrence was seen. In conclusion; Kugel Herniorrhapy which is a different approach to the preperitoneal space is essentially the same operation as the laparoscopic repair and it has similar results.
8th International Congress of the European-Association-for-Endoscopic-Surgery -- JUN 28-JUL 01, 2000 -- NICE, FRANCE
Keywords: Inguinal Herniorrhaphy; Trial